ROCK PHYSICS MODELING TO ANALYZE RELATIONSHIP BETWEEN CRITICAL POROSITY AND CONSOLIDATION FACTOR TO RESERVOIR QUALITY OF SANDSTONE, CIBULAKAN BAWAH FORMATION, NORTH WEST JAVA BASIN - MARCELINA (NIM: 12313040), BELLA
Reservoir quality is one of the important reference to do exploitation stage. Exploitation target should has good reservoir quality which is reflected by good porosity-permeability relationship. However, availability of permeability data is hard to get in every point of depth because of its expensive cost. So, this study will show elastic parameter which can be related to reservoir quality. In addition, clay content also affected reservoir quality. The higher clay content then reservoir quality is worse. This study is using data set of sandstone from Cibulakan Bawah Formation, North West Java Basin by rock physics modeling as its method. Nur model and Pride model is applied in this study. To do modeling, it needs elastic mineral modulus (Kmin and μmin) which is approached by Hashin-Shtrikman Average model, empirical of Raymer-Hunt-Gardner and Krief. The results of this study show elastic mineral modulus value ((Kmin and μmin) is 16.5 GPa and 23.5 GPa. Elastic parameter from Nur model and Pride model is reflected by ÃƒÂ˜/(1-(μdry/μmin)) and . Plotting to reservoir quality is more scatter than ÃƒÂ˜/(1-(μdry/μmin)). So, elastic parameter from Nur model is better to identify reservoir quality than elastic parameter from Pride and clay content also can be an indicator to identify reservoir quality.